Cardiovascular reflexes in patients after myocardial infarction. Effect of long-term treatment with beta-adrenoceptor antagonists. Issue 3 (September 1980) - Bennett, T; Wilcox, R G; Hampton, J R
Abstract : A double-blind study was made of men who had had a myocardial infarction at least one year previously, and who were being treated with propranolol, atenolol, or placebo. They were compared with age- and sex-matched control subjects. Under resting conditions, there were no differences between the systemic arterial blood pressures, forearm blood flows, or heart rates of the control subjects and the post-infarction patients treated with placebo. The patients, however, showed signs of reduced sympathetic effects on the cardiovascular system when their reflex responses to the Valsalva manoeuvre, lower body negative pressure, and performance of a mental task were assessed. Long-term treatment with propranolol or artenolol had little effect on resting systemic arterial blood pressure or forearm blood flow, but caused a significant reduction in resting heart rate. Differences in the reflex responses of these patients and those on placebo were attributable to the effects of the beta-adrenoceptor antagonists on resting heart rate. These results indicate that post-infarction patients do not have signs of overactivity of autonomic nervous control of the cardiovascular system. Furthermore, long-term treatment of such patients with beta-adrenoceptor antagonists does not impair cardiovascular reflexes.